2018
DOI: 10.1186/s40792-018-0553-x
|View full text |Cite
|
Sign up to set email alerts
|

Giant gastrointestinal stromal tumor of the mediastinum associated with an esophageal hiatal hernia and chest discomfort: a case report

Abstract: BackgroundGastrointestinal stromal tumors (GISTs) grow relatively slowly and without specific symptoms; therefore, they are typically incidental findings. We report a rare gastric GIST in the mediastinum associated with chest discomfort and an esophageal hiatal hernia.Case presentationAn 81-year-old woman with chest discomfort was admitted to the hospital, where barium esophagography showed a sliding esophageal hiatal hernia and a tumor of the lower esophagus and gastric wall. Esophagogastroscopy confirmed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is unclear why colon cancer in Morgagni hernias is much more common than in other diaphragmatic hernias. We have not found a single case of colon cancer associated with a type 4 hiatal hernia; however, large paraesophageal hernias have been found to contain gastric cancer [18] and other tumors such as gastrointestinal stromal tumors [19], with Wolfe et al reporting ovarian cancer metastases causing a symptomatic paraesophageal hernia [20]. One explanation for the differences seems to be the much higher incidence of ascending colon compared to descending colon cancer.…”
Section: Discussionmentioning
confidence: 67%
“…It is unclear why colon cancer in Morgagni hernias is much more common than in other diaphragmatic hernias. We have not found a single case of colon cancer associated with a type 4 hiatal hernia; however, large paraesophageal hernias have been found to contain gastric cancer [18] and other tumors such as gastrointestinal stromal tumors [19], with Wolfe et al reporting ovarian cancer metastases causing a symptomatic paraesophageal hernia [20]. One explanation for the differences seems to be the much higher incidence of ascending colon compared to descending colon cancer.…”
Section: Discussionmentioning
confidence: 67%
“…ere have been several studies showing that the coexistence between hiatal hernia and lower esophageal submucosal tumor was very common [1,7,12,13]. A case series on 66 patients who underwent surgery therapy for esophageal leiomyoma found that hiatal hernia presented in 15 (23%) patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…GISTs are 4 times more likely to recur if the primary site is the intestine compared to stomach. These data should be considered when evaluating success of surgical resection of recurrent tumors since the primary site could potentially condition the ultimate outcome in form of overall survival and recurrence-free survival [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%